Workplace stress management psychoeducation program to enhance employee resilience in the service industry - Kurnianingrum Ayu Miranti; Zamralita (University of Merdeka Malang, 2026)
Generation Z is increasingly entering the workforce and is known to be technologically adaptive; however, they are also vulnerable to workplace stress due to rapid organizational changes and high-performance demands, particularly in the service industry that requires intensive customer interaction and emotional labour. This community service program aimed to provide psychoeducation on workplace stress management for Generation Z employees at PT X, a professional organizing service company. The program was conducted through a 90-minute interactive webinar integrating psychoeducation, reflective discussion, and gamified learning activities. Program evaluation was conducted using pre-test and post-test assessments and participant satisfaction surveys. A total of 53 participants attended the webinar. The results showed an increase in knowledge scores from a pre-test mean of 40.00 to a post-test mean of 63.33, indicating a 58.3 percent improvement, while 91 percent of participants rated the program as relevant, useful, and easy to understand. Participants also reported increased awareness of emotional regulation and the application of adaptive coping strategies in the workplace. The findings indicate that webinar-based psychoeducation can effectively improve workplace stress management literacy and support workplace wellbeing among young employees in the service industry.